2020
DOI: 10.1186/s12885-020-06868-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HER2 induced myeloid cell alterations correspond with increasing vascular maturation in a murine model of HER2+ breast cancer

Abstract: Background: Therapy targeted to the human epidermal growth factor receptor type 2 (HER2) is used in combination with cytotoxic therapy in treatment of HER2+ breast cancer. Trastuzumab, a monoclonal antibody that targets HER2, has been shown pre-clinically to induce vascular changes that can increase delivery of chemotherapy. To quantify the role of immune modulation in treatment-induced vascular changes, this study identifies temporal changes in myeloid cell infiltration with corresponding vascular alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…CD45 histology staining revealed an increase in immune in ltration in treatment groups receiving trastuzumab. Previously collected data revealed trastuzumab has the potential to reprogram the immunosuppressive components of the tumor microenvironment and could contribute to anti-tumor responses [28]. Evaluation of immune cell characterization and impact on tumor regression using the present study's treatment regimen is needed to further elucidate mechanisms contributing to enhanced tumor regression in the combination treatment group.…”
Section: Discussionmentioning
confidence: 96%
“…CD45 histology staining revealed an increase in immune in ltration in treatment groups receiving trastuzumab. Previously collected data revealed trastuzumab has the potential to reprogram the immunosuppressive components of the tumor microenvironment and could contribute to anti-tumor responses [28]. Evaluation of immune cell characterization and impact on tumor regression using the present study's treatment regimen is needed to further elucidate mechanisms contributing to enhanced tumor regression in the combination treatment group.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, multiple cytokine expression would be an interesting future direction to explore in an in vivo tumor model comparing CD4 T-cell. Biological validation of T-cell immune in ltration can be achieved through ow cytometry against peripheral blood [20,[47][48][49]. Future experiments could investigate the involvement of the Fc-region of CD4+ T-cells and whether co-precipitation experiments can identify interaction between CD4+ T-cells and HER2+ breast cancer cells treated with trastuzumab.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FcgR-mediated stimulation of CD4+ T-cells and activation of CD4+ T-cells with HER2-primed dendritic cell vaccines reduced tumor burden through tumor-speci c T-cell response [18,19]. Although clinical studies have shown successful trastuzumab therapy is dependent on immune cell in ltration, there exists a lack of longitudinal studies that examine trastuzumab-induced CD4+ immune interaction with HER2+ breast cancer [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, FcgR-mediated stimulation of CD4+ T-cells and activation of CD4+ T-cells with HER2-primed dendritic cell vaccines reduced tumor burden through tumor-speci c T-cell response [18,19]. Although clinical studies have shown successful trastuzumab therapy is associated with immune cell in ltration, there exists a lack of longitudinal studies that examine trastuzumab-induced CD4+ immune interaction with HER2+ breast cancer [20].…”
Section: Introductionmentioning
confidence: 99%